A Chinese drug-compatibility-based approach to purslane hydrogels for acute eczema therapy - Wang, Ling; Zhang, Yuzhong; Geng, Shenglin; Ma, Lan; Wang, Yiran; Han, Dongxu; Fan, Guojuan; Zhang, Weifen; Lv, Yanna; Ma, Jinlong (Frontiers in Pharmacology, 2025)
Purslane (Portulaca oleracea L.) with heat-clearing and detoxicating, anti-inflammatory and resolving swelling, relieving itching and astringing function, has remarkable efficacy for acute eczema. However, most of the clinical applications of purslane are freshly prepared decoction, not as easy to apply as cream, because the decoction is easy to breed bacteria and easy to oxidize. Here, based on the theory of Chinese medicines compatibility, we made a purslane-tannic acid hydrogel (PL-HATA) by simple methods under mild conditions to solve the drawbacks of easy oxidation and inconvenience of use of Purslane. The antimicrobial activity of PL-HATA hydrogel can exert an excellent antimicrobial effect, reducing the flora on the skin of acute eczema and further relieving the symptoms of acute eczema. At the same time, it creates a normal reactive oxygen species (ROS) microenvironment for acute eczema and promotes recovery from acute eczema. It also improves the symptoms of acute eczema by promoting cell proliferation and migration. Importantly, it resulted in improved skin lesion scores, scratching behavior, eosinophil infiltration, swelling and inflammation levels, immune homeostasis, and histopathological changes in rats with acute eczema. Besides, HATA hydrogel is not only suitable for Purslane’s decocted metabolites but also for Purslane’s freshly squeezed metabolites. This purslane application protocol solved the drawbacks of Purslane’s decoction, improved its storage stability and convenience of use, which is the key issue to further promote its clinical application.